STRUKTUR KOMUNITAS GASTROPODA DI EKOSISTEM MANGROVE PANTAI KEJAWANAN: HUBUNGAN PARAMETER LINGKUNGAN TERHADAP KELIMPAHAN GASTROPODA - Yuandita, Tinta; Juliandri Prihadi, Donny; Sahidin, Asep; Sunarto, Sunarto; Sofyana, Neng Tanty; Syakilah, Salsabila Putri (Universitas Mataram, 2025)
This study aims to determine the structure of the gastropod community and the relationship between environmental parameters and gastropod abundance in the mangrove ecosystem of Kejawanan Beach. This study used a survey method using 10 x 10 m quadrant transects with 1 x 1 m subplots inside, with five points placed at each corner and in the center. The results of the study showed 12 families, including Potamididae, Littorinidae, Cerithiidae, Ellobiidae, Naticidae, Melongenidae, Coniidae, Nassariidae, Clavatulidae, Assimineidae, Ampullariidae, and Achatinidae. The total abundance of gastropods was 32.78 ind/m2. The diversity (H’) obtained falls into the moderate diversity category, with a value of 1.61. The evenness (E) obtained falls into the moderate evenness category and indicates a stable community, with a value of 0.62. The dominance (C) of gastropods indicates that no single species dominates across all research stations. The abundance of gastropods in the mangrove ecosystem of Kejawanan Beach shows a strong and positive relationship with environmental parameters such as silt fraction and salinity, and has a negative correlation with sand fraction and Dissolved Oxygen (DO).